Supply Chain Decisions and Coordination under the Combined Effect of Overconfidence and Fairness Concern. (25th April 2020) - Zhijian, Zhang; Wang, Peng; Wan, Miyu; Guo, Junhua; Liu, Jian
Abstract : The purpose of this study was to examine the joint effect of overconfidence and fairness concern on supply chain decisions and design contracts to achieve a win-win situation within the supply chain. For this study, a centralized supply chain model was established without considering the retailers' overconfidence and fairness concern. Furthermore, the retailers' overconfidence and fairness concerns were introduced into the decentralized supply chain, while the Stackelberg game model between the manufacturer and the retailer was built. Furthermore, an innovative supply chain contract, i.e., buyback contract, with promotional cost sharing was designed to achieve supply chain coordination along with overconfidence and fairness concern. Finally, a numerical analysis was also conducted to analyze the effect of overconfidence, fairness concern, and the validity of the contract. The principal findings of the study include the positive correlation between retailers' overconfidence and optimal order quantity, sales effort, expected utility, and profit. Although the order quantity and sales efforts were not affected by the fairness concern of the retailer, the contract achieved coordination with a win-win outcome when the level of overconfidence and fairness concern was moderate.